1999
DOI: 10.1007/s002130050934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early handling on amphetamine-induced locomotor activation and conditioned place preference in the adult rat

Abstract: Handled animals showed an attenuated CPP for amphetamine, data suggesting that sensitivity to the reward value of drugs of abuse in adulthood may be susceptible to relatively minor environmental manipulations early in life. This effect of handling on CPP does not seem to reflect differences in locomotor sensitivity to amphetamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 45 publications
2
34
0
2
Order By: Relevance
“…All these behavioral effects of early handling may well increase an animal's willingness to interact with pups. The role of altered endocrinology in the behavioral effects are not at present clear, however, with some investigators finding an effect of early handling on open-field and other "emotion" tests (Caldji et al, 2000;Caldji et al, 1998;Meerlo, Horvath, Nagy, Bohus, & Koolhaas, 1999) and others finding no effect (Campbell & Spear, 1999).…”
Section: Effects Of Short Periods Of Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…All these behavioral effects of early handling may well increase an animal's willingness to interact with pups. The role of altered endocrinology in the behavioral effects are not at present clear, however, with some investigators finding an effect of early handling on open-field and other "emotion" tests (Caldji et al, 2000;Caldji et al, 1998;Meerlo, Horvath, Nagy, Bohus, & Koolhaas, 1999) and others finding no effect (Campbell & Spear, 1999).…”
Section: Effects Of Short Periods Of Separationmentioning
confidence: 99%
“…privation produces increased (Caldji et al, 2000) or no (Campbell & Spear, 1999;Lehmann, Pryce, Bettschen, & Feldon, 1999;Lovic et al, 2001) change in "fear" and "emotionality," as assessed by adult open-field activity and plus-maze performance. Despite these problems of interpretation,there is a substantial literature showing that early deprivation from mothers and the nest have long-term effects on the development of the animals' hypothalamic-pituitary-adrenal (HPA) system and responses to stressors (Anisman, Zaharia, Meaney, & Merali, 1998;Plotsky & Meaney, 1993).…”
mentioning
confidence: 99%
“…Results indicated, however, that the magnitude of Mn-induced toxicity in the nucleus accumbens, and other relevant brain regions, was apparently insufficient to impair performance on the CPP task. Additionally, CPP performance has been reported to vary according to sex, with female rats and mice showing more robust place preferences than males (Russo et al, 2003;Balda et al, 2006; but see Crawford et al, 1995;Campbell and Spear, 1999). For this reason we included both sexes in the CPP experiment but found that (a) Mn did not differentially affect place preference conditioning of male and female rats, and (b) preference testing and reinstatement performance did not differ according to sex (perhaps due to insufficient n).…”
Section: Discussionmentioning
confidence: 99%
“…Campbell and Spear (1999) found that brief neonatal isolation attenuates amphetamine CPP during early adulthood. With cocaine self-administration, MS15 male and female rats fail to acquire cocaine self-administration with a unit dose (0.0625 mg/kg per infusion) that supports self-administration in controls and MS180 rats .…”
Section: B Social Influencesmentioning
confidence: 95%